Implementasi LKPD Berbasis Higher Order Thinking Skills (HOTS) dengan Pictorial Riddle untuk Hasil Belajar Biologi - Azizah, Alfiana Nur; Utami, Sri; Kiswardianta, R. Bekti (Bioscientist : Jurnal Ilmiah Biologi, 2023)
This study aims to examine the application of LKPD (Learner Worksheets) focusing on Higher Order Thinking Skills (HOTS) using Pictorial Riddle (image-based riddles) to increase interest and learning outcomes in biology class VII at MTs An-Najihah, Kerjo Mojorejo Village, Kebonsari District, Madiun Regency on Animal and Plant Tissue Sub-Material. This research uses Classroom Action Research (PTK). There are 4 data collection techniques in this study, namely interviews, observations, tests and documentation. The use of HOTS-based LKPD with Pictorial Riddle is able to improve learning outcomes and student interest in the sub-material of Animal and Plant Tissues in class VII MTs An-Najihah. The completeness of students has increased in each cycle. In the pre-cycle of individual completeness amounted to 11 students and 32% classical completeness, in cycle I individual completeness amounted to 15 students and classical completeness to 43%. Then in cycle II individual completeness increased to 32 students and classical completeness to 91%. The conclusion of the research is that the implementation of HOTS-based LKPD with Pictorial Riddle can increase the interest and learning outcomes of VII grade students of MTs An-Najihah on the subject matter of Animal and Plant Tissues.